Impacto em renda do microcrédito: uma investigação empírica sobre geração de renda do Crédito Popular Solidário (São Paulo Confia), no município de São Paulo - Monzoni Neto, Mario Prestes (2006)
This contribution presents an empirical investigation of the impact of micro-credit initiatives based on data collected from clients from three units (Brasilândia, Jardim Helena, and Heliópolis) of the Crédito Popular Solidário (São Paulo Confia). The Crédito Popular Solidário is a Public Private Partnership established with the participation of the city of São Paulo. The findings demonstrate the micro-credit plays a minor role in the Brazilian economy, especially in comparison to certain nations of southeast Asia or even other Latin American countries. Given the minor degree of penetration, as viewed in either absolute or relative terms, micro-credit initiatives have an enormous potential in the economic development of Brazil. Statistical analysis of the financial and economic data demonstrates the significant impact of micro-credit initiatives on income generation – they doubled the income of small scale entrepreneurs in two years time. In addition, the average rate of internal return generated by the credit granted is such that the actual interest rate (capital costs) levied by the São Paulo Confia, and the market is irrelevant. Results reveal that small scale entrepreneurs in low-income neighborhoods in São Paulo are in such dire need of capital that any injection of liquidity, especially to cover working capital needs, is a tremendous stimulus for future returns and income generation. In other words, labor is available, but there is a lack of capital to generate production. As a result of capital injection, the recipients of micro-loans are able to boost their income to a level accepted by the banking system. This analysis and the results of this contribution represent an opportunity for public administrators to consider the use of micro-credit initiatives as a policy tool for income generation, among other alternatives in Brazilian social policy. Also, for the financial institutions to realize that these initiatives could bring new clients with a good credit history to the banking system.